أثر الطلاق على حقوق الاولاد - حسن, نادية علي (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The research dealt with the impact of divorce on the rights of children, and dealt with the definition of divorce and its causes, as well as an indication of the most important rights of children on parents and the extent of the impact of divorce on those rights, and in conclusion with the results and proposals.